Importance of antioxidant protection during chronicle cerebral ishemia - M. V. Popov; L. A. Klimova (Бюллетень сибирской медицины, 2009)
The relation between the clinical presentation of the chronicle cerebral ischemia and condition of reactions of lipid peroxidation during the prolong treatment is found out. It is characterized the reduction of the intensity of the lipid peroxidation and substantial increased of the level of the both enzymatic oxidation preventives and non enzymatic oxidation preventives.